SON connects the splicing-regulatory network with pluripotency in human embryonic stem cells - Lu, Xinyi (2016)
Human embryonic stem cells (hESCs) harbour the ability to undergo lineage-specific differentiation into clinically relevant cell types. Transcription factors and epigenetic modifiers are known to play important roles in the maintenance of pluripotency of hESCs. However, little is known about regulation of pluripotency through splicing. In this study, we identify the spliceosome-associated factor SON as a factor essential for the maintenance of hESCs. Depletion of SON in hESCs results in the loss of pluripotency and cell death. Using genome-wide RNA profiling, we identified transcripts that are regulated by SON. Importantly, we confirmed that SON regulates the proper splicing of transcripts encoding for pluripotency regulators such as OCT4, PRDM14, E4F1 and MED24. Furthermore, we show that SON is bound to these transcripts in vivo. In summary, we connect a splicing-regulatory network for accurate transcript production to the maintenance of pluripotency and self-renewal of hESCs.